Comparison of the ipsi-lateral versus contra-lateral retrograde approach of percutaneous coronary interventions in chronic total occlusions - Mashayekhi, Kambis; Behnes, Michael; Akın, Ibrahim (Catheterization and cardiovascular interventions, 2017)
Background Retrograde recanalization of coronary chronic total occlusions (CTO) via contralateral (CL) collateral connections (CCs) is successful in 60-70% of patients in whom conventional antegrade approach fails or is unpromising. This study describes our experience with retrograde CTO-PCI via ipsi-lateral (IL) CCs in patients with unfavorable CL CCs. Methods Between January 2013 and September 2015, 392 consecutive CTO procedures were performed by two high volume CTO-operators and the relevant data were fed into an online registry (ERCTO® EuroCTO-club). Most patients (222/392; 57%) were approached antegradely, whereas 43% were attempted retrogradely (170/392). After exclusion of all procedures performed via bypass-grafts (n = 12), PCI via CL CCs, the CL-group (n = 114/158; 72%), was compared with the IL-group that was attempted via IL CCs (n = 44/158; 28%). Results Both groups were similar with respect to risk factors and morphologic criteria of CTO-severity. The initial primary strategy was successful in 78% in the CL-group and in 68% in the IL-group. In both patient groups, the initial strategy had to be switched in five patients from CL toward IL (4.4%, n = 5/114) and from IL to CL (11.3% n = 5/44). The rate of major complications was 7% (CL) and 5% (IL), respectively (n.s.). After retrograde failure and cross-over to an antegrade controlled re-entry strategy the overall success rates increased to 92% (CL) and 93% (IL). Conclusions In experienced hands retrograde CTO-PCI via IL CCs appears as safe and successful as the CL approach. © 2016 Wiley Periodicals, Inc.